2021
DOI: 10.3390/biology10111197
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic D76N Variant of β2-Microglobulin: Synergy of Diverse Effects in Both the Native and Amyloid States

Abstract: β2-microglobulin (β2m), the light chain of the MHC-I complex, is associated with dialysis-related amyloidosis (DRA). Recently, a hereditary systemic amyloidosis was discovered, caused by a naturally occurring D76N β2m variant, which showed a structure remarkably similar to the wild-type (WT) protein, albeit with decreased thermodynamic stability and increased amyloidogenicity. Here, we investigated the role of the D76N mutation in the amyloid formation of β2m by point mutations affecting the Asp76-Lys41 ion-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…β 2 -Microglobulin (β2m) is the light chain of the major histocompatibility complex I. Dissociating from the complex, the protein circulates in monomeric form in the blood and is associated with dialysis related amyloidosis in long-term haemodialysis patients. In 2012, a variant of the protein carrying a D76N point mutation was discovered causing a hereditary systemic amyloidosis with pathophysiology strikingly different from that of the wild-type protein ( 39 , 40 ). The first investigations found that the mutant exhibits a high-resolution structure almost identical to that of the wild-type protein (Figure 2D ) and its unique behavior can be discovered by using a rather complex methodology.…”
Section: Resultsmentioning
confidence: 99%
“…β 2 -Microglobulin (β2m) is the light chain of the major histocompatibility complex I. Dissociating from the complex, the protein circulates in monomeric form in the blood and is associated with dialysis related amyloidosis in long-term haemodialysis patients. In 2012, a variant of the protein carrying a D76N point mutation was discovered causing a hereditary systemic amyloidosis with pathophysiology strikingly different from that of the wild-type protein ( 39 , 40 ). The first investigations found that the mutant exhibits a high-resolution structure almost identical to that of the wild-type protein (Figure 2D ) and its unique behavior can be discovered by using a rather complex methodology.…”
Section: Resultsmentioning
confidence: 99%
“…3 A ). Indeed, a recent study has highlighted the importance of this salt bridge for D76N-β 2 m stability and aggregation ( 47 ). Interestingly, two of the most rapidly aggregating variants (D76N- and D76Q-β 2 m) share an amide sidechain.…”
Section: Resultsmentioning
confidence: 99%
“…Leukocyte immunoglobulin-like receptor B (LILRB) is expressed in most immune cells, and in binding to the major ligand major histocompatibility complex I (MHCI), mediates the negative regulation of immune cell activation [ 50 , 51 ]. MHCI is a complex formed by the HLAα chain and β 2-microglobulin (β2 M) [ 52 ]. Anchored by glycosyl phosphatidylinositol, CD24 interacts with sialic acid, binding immunoglobulin-like agglutinin-10 (SIGlec-10) to β2 M, which is overexpressed in some tumor tissues and binds to LILRB1 on macrophages to inhibit phagocytosis, resulting in a loss of immune surveillance [ 53 , 54 ].…”
Section: Classification and Mechanisms Of The Antitumor Action Of Icismentioning
confidence: 99%